BUDIDAYA JAMUR TIRAM DAN PENGOLAHAN NYA MENJADI ANEKA PRODUK SEBAGAI ALTERNATIF BERWIRAUSAHA - Setia Iriyanto (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Oyster Mushroom Cultivation and Processing Miscellaneous Products from Oyster Mushrooms In Pekalongan aims to foster the spirit and skills of entrepreneurship in the field of oyster mushroom cultivation and processing of various products made from oyster mushrooms for marginalized groups as a result of layoffs, low education, bankruptcy business, convalescents stroke ever experienced, etc. are mutually neighbors and groups in order to supplement the family income in order to improve their welfare, in empowerment is implemented in stages and begins with an orientation program, motivate entrepreneurship, education and training of production management / oyster mushroom cultivation, financial management and marketing, and the practice of making kumbung / mushroom houses are equipped with shelves to put baglog / seedlings mushroom, oyster mushroom cultivation training into a variety of products, as well as the purchase baglog / mushroom seed production and processing equipment. Empowerment implementation began in early March 2016 and aims at empowering the two (2) groups each consisting of 5 persons will be formed groups Joint Venture (KUBE) Oyster Mushroom Cultivation who produce oyster mushroom producing oyster mushrooms producing oyster mushrooms and oyster mushrooms produce KUBE Miscellaneous products Processing / Food of oyster mushroom in the form of flakes, Pepes, nuggets, etc.Keywords: entrepreneurship, oyster mushrooms, a variety of refined products.